ChemInform Abstract: Fmoc‐Modified Amino Acids and Short Peptides: Simple Bio‐Inspired Building Blocks for the Fabrication of Functional Materials. Issue 36 (August 2016) - Tao, Kai; Levin, Aviad; Adler‐Abramovich, Lihi; Gazit, Ehud
Abstract: Review: studies on the self‐assembly of Fmoc‐modified biomolecules and their relevant applications in diverse advanced fields; 167 refs.